Activating collective agency in disrupted contexts: The social-cognitive context of ad hoc organising in a small and medium-sized enterprise. (March 2022) - Ho, Marcus; Teo, Stephen T T
'Ad hoc organising' is becoming an increasingly important topic in the growing literature on disrupted contexts. It is viewed as an emergent, largely unpredictable phenomenon. However, few theoretical frameworks exist for understanding how small and medium-sized enterprises (SMEs) engage in ad hoc organising, via the convergence of people and organisations, to alleviate suffering in a disrupted context. In this inductive, theory-building, multiple case study, we explore the way collective agency in an SME emerges in the process of ad hoc organising. Our findings identify two overlapping micro-processes that enable collective agency in a disrupted context: building collective efficacy and initiating communal coping. Together, these micro-processes lead to SME leaders achieving collective outcomes for the community in ad hoc organising. We discuss these findings in relation to the literature on ad hoc organising and SMEs in disrupted contexts.